2013
DOI: 10.1590/0037-8682-0056-2012
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the spatiotemporal distribution of American cutaneous leishmaniasis in counties located along road and railway corridors in the State of Maranhao, Brazil

Abstract: Introduction:The incidence of American cutaneous leishmaniasis (ACL) is increasing in Latin America, especially in Brazil, where 256,587 cases were confi rmed in the last decade. Methods: This study used a Bayesian model to examine the spatial and temporal distribution of ACL cases between 2000 and 2009 in 61 counties of State of Maranhão located along the three main road and railway corridors. Results: During the study period, 13,818 cases of ACL were recorded. There was a signifi cant decrease in the inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Noteworthy, the significant number of cases in the peri-urban zone of Caxias, near major transportation routes such as the BR-316, the state railroad, and the highway network (MA 127, MA 349, and MA 034) may play a role in the expansion of the disease occurrence, given the high flow of people in this area. As an example, a study conducted between 2000 and 2009 in 61 municipalities in the state of Maranhão located along the three main road and state rail corridors concluded that these could markedly influence the disease dissemination and maintenance (Gonçalves Neto et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy, the significant number of cases in the peri-urban zone of Caxias, near major transportation routes such as the BR-316, the state railroad, and the highway network (MA 127, MA 349, and MA 034) may play a role in the expansion of the disease occurrence, given the high flow of people in this area. As an example, a study conducted between 2000 and 2009 in 61 municipalities in the state of Maranhão located along the three main road and state rail corridors concluded that these could markedly influence the disease dissemination and maintenance (Gonçalves Neto et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is also one of the states with the highest indicators of poverty in the country, which is observed both at urban and rural areas (Sobel et al, 2010;Tronco and Ramos, 2017). Such factors associated with the increasing rates of migration and ecotourism in the region are critically important in the epidemiology of this neglected disease (Gonçalves Neto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Neto et al . 10 analyzed 13,818 cases from 2000 to 2009 along a transcontinental railroad in Maranhao State and found clusters of CL cases and a high risk of CL, influenced by the Amazon forest, along the railway line II located in the Western region of the State.…”
Section: Resultsmentioning
confidence: 99%
“…In the study conducted by Neto et al . 10 , the area with the highest incidence of CL was in the Western region of the Maranhao State, which is influenced by the Amazon forest. The climate and vegetation of the forest favor a greater diversity of vector species, reservoirs and etiological agents 22 .…”
Section: Discussionmentioning
confidence: 97%
“…The peripheral areas of cities lack adequate infrastructure (absent or inadequate basic sanitation, unpaved streets, etc.). These areas are also typifi ed by the presence of chicken coops next to homes, abundant trees, concentrations of animals in and around the home and overcrowding under conditions of inequality, all of which favor the expansion of the vector and the disease (13) (22) (34) (38) (39) (40) (41) (42) . This fi nding may prove useful in improving control and surveillance measures, because the prioritized development of these activities in the city's periphery could render VL control programs more effective.…”
Section: Discussionmentioning
confidence: 99%